2016
DOI: 10.1007/s00710-016-0437-3
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping and statistical evaluation of fracture minerals in the granitic bedrock at Forsmark, Sweden

Abstract: This article provides quantitative data on occurrences and amounts of fracture minerals that coat discrete fractures in granitic rock at the Forsmark site in Sweden. The data are useful for retardation modelling of radionuclide and other contaminants, and for groundwater composition calculations. In a unique campaign, 2071 open fractures in groundwater conducting rock have been mapped with respect to chlorite, calcite, and pyrite. In total 767 m of drill core has been studied from very shallow rock down to~100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This observation raises the possibility that many of these fractures are inherited from prior deformation, affected by geologic heterogeneity (e.g., lithologic variation), or influenced by sources of stress we have not accounted for in our model. Many of the fractures contain secondary minerals, precipitated from hydrothermal fluids under antecedent conditions, but some fractures coated or filled by calcite, clay minerals, or Fe oxides indicate low‐temperature water‐rock interaction, possibly also during the Quaternary (Drake et al, 2009; Löfgren & Sidborn, 2016; Sandström & Tullborg, 2009). The good correspondence between failure proxies and F open indicates that the present‐day stress field contributes to reactivating and opening these existing fractures and allowing water‐rock interaction.…”
Section: Comparison Of Stress Model Results With Fracture Databasementioning
confidence: 99%
See 1 more Smart Citation
“…This observation raises the possibility that many of these fractures are inherited from prior deformation, affected by geologic heterogeneity (e.g., lithologic variation), or influenced by sources of stress we have not accounted for in our model. Many of the fractures contain secondary minerals, precipitated from hydrothermal fluids under antecedent conditions, but some fractures coated or filled by calcite, clay minerals, or Fe oxides indicate low‐temperature water‐rock interaction, possibly also during the Quaternary (Drake et al, 2009; Löfgren & Sidborn, 2016; Sandström & Tullborg, 2009). The good correspondence between failure proxies and F open indicates that the present‐day stress field contributes to reactivating and opening these existing fractures and allowing water‐rock interaction.…”
Section: Comparison Of Stress Model Results With Fracture Databasementioning
confidence: 99%
“…Our stress model includes simplifying assumptions about material properties (e.g., linear elasticity, homogeneity, and isotropy) and ambient regional stress (e.g., spatially uniform regional horizontal stresses within rock masses separated by the Singö deformation zone). The bedrock at Forsmark has variable lithology, multiple deformation zones, multiple generations of fracture fillings and coatings, and a time‐varying stress history that spans 1.89 Ga and most recently includes Quaternary glaciations and deglaciations (Drake et al, 2009; Hall et al, 2019; Löfgren & Sidborn, 2016; Lönnqvist & Hökmark, 2013; Martin, 2007; Stephens et al, 2015). Previous studies have indicated that increased pore pressure associated with glacially induced hydraulic jacking may open subhorizontal fractures with large apertures (>1 cm) as deep as 200 m (Lönnqvist & Hökmark, 2013) and may influence groundwater geochemistry and support microbial life as deep as 500 m (Tullborg et al, 2017).…”
Section: Connections Between the Subsurface Stress Field And Fracture Opennessmentioning
confidence: 99%
“…Secondary minerals may coat the fracture surface and other precipitates; the original rock matrix near the surface may be mechanically disturbed when the fracture formed and may be also chemically altered in various ways. These alterations seldom extend more than a few millimeters, but on occasion can extend several centimeters in granitoid rocks [ Löfgren and Sidborn , ]. The alterations are practically always as porous as, or more porous than the rock matrix at larger distances from the fracture face.…”
Section: Hydrologic Issues Related To Nuclear Waste Repository In Crymentioning
confidence: 99%
“…At the two study sites (Laxemar and Forsmark), which are located on the east coast of Sweden, the bedrock is composed of Paleoproterozoic crystalline bedrock (Figure S1) that comprise a complex network of fractures. , The frequency of open fractures is generally higher in Laxemar than in Forsmark, higher in the upper part of the bedrock (0–100 m) than in the deeper part, and in Laxemar higher in the upper 10–15 m (nearly 3 open fractures per meter) than in the deeper counterparts (∼1–1.5/m) . The latter feature is due to stress relaxation in Holocene caused by unloading of the Weichselian continental ice sheet.…”
Section: Methodsmentioning
confidence: 99%